2005
DOI: 10.1139/x05-166
|View full text |Cite
|
Sign up to set email alerts
|

The physiological responses of oak seedlings to warm storage

Abstract: The effects of warm storage (15 °C) on the physiological responses and subsequent field performance of 2-year-old oak (Quercus robur L.) seedlings that had been cold (1–2 °C) stored until May were assessed. Shoot xylem pressure potential, shoot water content, shoot tip dry mass, root electrolyte leakage, and root growth potential were evaluated at regular intervals during the 21-day warm storage period. The date of lifting to cold storage had little effect on the physiological responses to warm storage. Root e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…These factors have each been shown to affect seedling vigor and survival (Ritchie et al, 1985;Puttonen, 1987;Lindqvist, 2001;Cabral and O'Reilly, 2005). However, neither factor substantially affected seedling survival in this study.…”
Section: Survival As Affected By Planting Datementioning
confidence: 55%
“…These factors have each been shown to affect seedling vigor and survival (Ritchie et al, 1985;Puttonen, 1987;Lindqvist, 2001;Cabral and O'Reilly, 2005). However, neither factor substantially affected seedling survival in this study.…”
Section: Survival As Affected By Planting Datementioning
confidence: 55%
“…Simulated ambient storage at 158C for 21 days increased REL in pedunculate oak (Quercus robur L.) and Douglas fir seedlings, but the results were not consistent with post-planting performance Cabral & O'Reilly, 2005). When Douglas fir seedlings were placed in warm storage for 21 days REL increased from 47 -63% for seedlings lifted in October and from 38 -58% in December.…”
Section: Ambient Storage (Cool To Warm Temperatures)mentioning
confidence: 88%
“…However, REL was considered to be a poor indicator of survival potential survival . In pedunculate oak, REL oscillated during warm storage (Cabral & O'Reilly, 2005). For example, although a 21-day warm storage period reduced plant quality in oak, REL actually declined during the final 7 -10 days of storage was measured over the course of 21 days and REL values went up and down, i.e.…”
Section: Ambient Storage (Cool To Warm Temperatures)mentioning
confidence: 99%
“…Water relations (Ameglio et al, 2001), bud mitotic activity (Calme et al, 1994), abscisic acid concentration (Li et al, 2003), soluble sugar concentration (Tinus et al, 2000), and chlorophyll fluorescence (Rose and Haase, 2002) are among the many physiological indicators used for conifers. Though these measurements are rapid, they have had limited application in hardwood regeneration programs (Cabral and O'Reilly, 2005;Généré et al, 2004;O'Reilly et al, 2003;Radoglou and Raftoyannis, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…The electrolyte leakage (EL) method, used extensively as a reliable approach to determine cold hardiness in conifer research (Bigras, 1997;Colombo et al, 1995;Jacobs et al, 2008;Tinus and Burr, 1997), was chosen for this study as it has recently shown success with hardwood seedlings (Cabral and O'Reilly, 2005;Garriou et al, 2000;Généré et al, 2004;Mortazavi et al, 2004;O'Reilly et al, 2003;Radoglou and Raftoyannis, 2001). Cold temperatures reduce enzymatic activity, alter metabolism, and decrease photosynthetic capacity of plant tissues (Dubey, 1997).…”
Section: Introductionmentioning
confidence: 99%